Endoplasmic Reticulum Stress: Its Role in Disease and Novel Prospects for Therapy - Axel H. Schönthal (Scientifica)
The endoplasmic reticulum (ER) is a multifunctional organelle required for lipid biosynthesis, calcium storage, and protein folding and processing. A number of physiological and pathological conditions, as well as a variety of pharmacological agents, are able to disturb proper ER function and thereby cause ER stress, which severely impairs protein folding and therefore poses the risk of proteotoxicity. Specific triggers for ER stress include, for example, particular intracellular alterations (e.g., calcium or redox imbalances), certain microenvironmental conditions (e.g., hypoglycemia, hypoxia, and acidosis), high-fat and high-sugar diet, a variety of natural compounds (e.g., thapsigargin, tunicamycin, and geldanamycin), and several prescription drugs (e.g., bortezomib/Velcade, celecoxib/Celebrex, and nelfinavir/Viracept). The cell reacts to ER stress by initiating a defensive process, called the unfolded protein response (UPR), which is comprised of cellular mechanisms aimed at adaptation and safeguarding cellular survival or, in cases of excessively severe stress, at initiation of apoptosis and elimination of the faulty cell. In recent years, this dichotomic stress response system has been linked to several human diseases, and efforts are underway to develop approaches to exploit ER stress mechanisms for therapy. For example, obesity and type 2 diabetes have been linked to ER stress-induced failure of insulin-producing pancreatic beta cells, and current research efforts are aimed at developing drugs that ameliorate cellular stress and thereby protect beta cell function. Other studies seek to pharmacologically aggravate chronic ER stress in cancer cells in order to enhance apoptosis and achieve tumor cell death. In the following, these principles will be presented and discussed.